171k views
2 votes
(10x^2)^-3
Simplify the exponential equation

2 Answers

2 votes

Answer:

= 10x⁻⁶

Explanation:

2*-3 = -6

then:


10x^{2^(-3)} = 10x^(-6)

= 10x⁻⁶

User Justin Carter
by
5.8k points
4 votes

Simplifying an exponential equation can be done by using different laws of exponents.

In this case, we can use the power rule and negative exponent rule

Power rule:


(a^x)^y=a^x^y

Negative exponent rule:


a^-^y=(1)/(a^y)

1. Use the negative exponent rule


(10x^2)^-^3=(1)/((10x^2)^3)

2. Use the power rule and simplify

  • -3 has to be applied to 10 and x^2


10^3=1000 and
(x^2)^3=x^6


(1)/(1000x^6)

User Larry Wang
by
5.1k points